The Psychological Dimensions of the Recipient's Participation in Contemporary Plastic Arts Exhibitions - AlKabi, Kareem Mohsen Ali Sameer (Dirasat: Human and Social Sciences, 2025)
Objective: This study aims to identify the psychological dimensions of the recipient's participation in contemporary plastic arts exhibitions. Methods: The study was conducted on a research community of (28) contemporary plastic arts exhibitions. The researcher deliberately selected (3) contemporary plastic arts exhibitions in America and Europe as a sample for the current research to achieve its goal, then analyzed the research sample by adopting the descriptive analytical approach. Results: The psychological dimensions of the recipient's participation in contemporary plastic arts exhibitions were revealed through direct interaction between the recipient and the artwork by means of play and recreation. Transcendence had a strong presence as an active psychological dimension in these exhibitions. Moreover, the recipient’s participation in the aforementioned exhibitions contributed to creating a relational pattern between the general public and art by endeavoring to provide the public with the opportunity to participate in the production of artistic works. Conclusion: The study concludes that the recipient’s participation can be considered a culture that is present in contemporary plastic arts exhibitions, which offer a means to attract the general public. In addition, the use of contemporary technology in art has led to the interaction of genres of art in the same exhibitions.